Chronic Abdominal Pain in Children and Adolescents: Parental Threat Perception Plays a Major Role in Seeking Medical Consultations. (24th November 2016) - Calvano, Claudia; Warschburger, Petra
Abstract : Background . Pain symptoms, associated impairment, and parental perception of threat are reported to be predictors of health care utilization (HCU) in childhood chronic abdominal pain (CAP). However, mediating variables and their interrelations have not yet been systematically studied. Objectives . This study aims to identify mediating pathways of influence between child's abdominal pain and the number of pain-related medical visits. Methods . In a multicenter study, we recruited N = 151 parent-child dyads with children aged 6–17 years suffering from CAP. A composite measure of pain symptoms was defined as predictor and the number of pain-related medical visits as outcome variable. This relation was analyzed by serial mediation, including child- and parent-reported impairment and parental threat perception as mediators. Results . Only parental threat perception significantly linked child's pain symptoms to the number of medical visits. Measures of impairment did not have a significant effect. Conclusions . Parental pain-related threat perception is strongly related to health care seeking in childhood CAP. Addressing threat perception might be a fruitful parent-centered approach in clinical practice.